Additional data on Spinitectus petterae (Nematoda: Rhabditida) from Clarias gariepinus (Siluriformes: Clariidae) in the Vaal River system: conserved morphology or high intraspecific genetic variability? - Austin, Lucinda; Dos Santos, Quinton Marco; Avenant-Oldewage, Annemarie (Folia parasitologica, 2023)
Two species of Spinitectus Fourment, 1884 have been recorded from southern Africa, namely Spinitectus polli Campana-Rouget, 1961 and Spinitectus petterae Boomker, 1993, both from the Limpopo River system. Spinitectus petterae was described from North African catfish, Clarias gariepinus (Burchell), whereas S. polli infects squeakers, Synodontis spp. During parasitological surveys in the Vaal River system (Orange River catchment), Spinitectus specimens were collected from C. gariepinus. These systems are adjacent but not connected. Therefore, this study aimed to identify the specimens collected using morphological and molecular techniques. The morphological study included light and scanning electron microscopy of whole specimens and excised spicules. Specimens were genetically characterised using 18S rDNA, 28S rDNA and cox1 mtDNA. Additionally, immature specimens of S. petterae were collected near the type locality. Morphological characteristics were most similar to S. petterae from C. gariepinus, whereas genetic data were dissimilar to all available data for the genus. Additional morphological characteristics noted for S. petterae in the present study were the details of the left and right spicule structure and the porous structures on the pseudolabia. Specimens from the Vaal River system differed from those originally described as S. petterae by additional spines posterior to the third ring, lacking caudal alae and variable total body and male oesophagus length. Based on 18S rDNA, haplotypes from the type locality varied only slightly from the study material, supporting the morphological identification. However, 28S rDNA and, more conspicuously, cox1 mtDNA displayed substantial variation between specimens from these localities, which needs further investigation. Haplotypes generated in the present study were highly dissimilar to those characterised for S. petterae from Tanzania and Egypt. Nevertheless, the nematodes collected from C. gariepinus in the Vaal River system are considered S. petterae. This study expands the geographical distribution and adds additional morphological and genetic information for S. petterae, contributing to the limited knowledge of African species of Spinitectus.
Keywords: Microscopy, Electron, Scanning; Spiruroidea; Rhabdochonidae; African sharptooth catfish; South Africa; sumci; mikroskopie elektronová rastrovací; mužské pohlaví; Rhabditida; DNA, Ribosomal; řeky; Rivers; Crocodile River; zvířata; Catfishes; ribozomální DNA; DNA barcoding.; Vaal Dam; Male; Animals